Acid-peptic diseases of the stomach and duodenum including Helicobacter pylori and NSAIDs - Crowe, Sheila (Henry Stewart Talks, 2014)
Clinical presentations of H. pylori infection, Upper GI diseases and H. pylori infections, Microbiologic factors, Epidemiology/transmission, Pathophysiologic factors, H. pylori gastritis: pathology findings, Peptic ulcer disease (PUD), Duodenal ulcer, Gastric ulcer, NSAIDs and ulcer formation, H. pylori treatment and ulcer eradication, Non-ulcer dyspepsia and H. pylori treatment, Antrum-predominant gastritis and acid reflux, Corpus-predominant gastritis and acid reflux, Gastric adenocarcinoma, Gastric lymphoma, When and whom to test for H. pylori infection?, ACG criteria for testing, Maastricht III & IV criteria for testing, Diagnostic tests, Noninvasive testing, Sequential therapy, Antibiotic resistance in the treatment of H. pylori, H. pylori vaccination
Updated at 2022/03/21